A descriptive study of a novel pharmacist led health outreach service for those experiencing homelessness. (8th March 2019) - Lowrie, Frances; Gibson, Lauren; Towle, Ian; Lowrie, Richard
Abstract: Objectives: To illustrate and review this new service and to describe the demographics of the patient group and the typology of interventions made by the pharmacist prescribers. Methods: Pharmacists provided pop-up, drop-in (no appointment needed) health clinics to various homeless support venues in Glasgow City Centre. Data from pharmacists' interventions ( n = 52) and patient demographics were gathered from clinical records. Data were then extracted, transcribed and analysed. Key findings: The demographics of the homeless patient group consisted mainly of white middle-aged males (mean age 39.8 years), of Scottish ethnicity and living in homeless hostels. Medications were prescribed by pharmacists in 62% of all patients. New medications were initiated in 69% of these patients; repeat/re-issues of lapsed medications were issued in 66% of these patients; changes were made to existing medication in 16%. The most commonly prescribed items were as follows: wound dressings; antihypertensives; antidiabetics; analgesics; inhalers; antidepressants; and nutritional supplements. Pharmacists diagnosed a new clinical issue in 69% of patients, most commonly with infections (skin or respiratory) in 36% of patients. Sixty-two per cent of patients had their presenting symptoms managed by the pharmacist alone. Patient engagement was good with 85% subsequently attending either a follow-up with the pharmacist or onward referral (to specialist services, secondary care, general practitioner appointment etc). Conclusions: Assertive outreach by pharmacist independent prescribers for people who are homeless is feasible and leads to increased access to medicines for acute and chronic health problems. Further work is needed to evaluate the impact of this new service on key clinical outcomes.